Exploring the factors that contribute to attitude change in communication among young adults - Gim, Yuen Ching; Gwee, Jing Xuan; Ho, Wai Khang; Lee, Say Yik; Lim, Tiong Lei (2018)
The study explored on the factors that contribute to attitude change among young adults in communication by constructing three different objectives. First, is to study the people understanding on persuasive communication. Secondly, researchers determine the factors that influencing young adults’ attitude change in communications. In addition, researchers also find out the biggest communications influencer on young adults’ attitude change. The data was collected through semi-structured interview that conducted through five informants using non-probability sampling as the sampling technique where subject have been selected were based on the convenience of accessibility and proximity of researchers. The information selection was young adults aged between 20 to 30 years old regardless race and gender. The research had found parents, peers, media, personage and environment are the factors that contribute to young adults’ attitude change in communication. However, peers was found to have the biggest influence in the research than other factors.